Validation of a Patient Global Assessment for extent, severity and impact to define the severity strata for the Self Assessment Vitiligo Extent Score (SA‐VES). (1st September 2020) - van Geel, N.; Uitentuis, S.E.; Zuidgeest, M.; Wolkerstorfer, A.; Bekkenk, M.W.; Moock, C.; Van Goethem, C.; Verlaeckt, E.; Smet, C.; Grine, L.; Speeckaert, R.
Abstract: Background: The Self Assessment Vitiligo Extent Score (SA‐VES) is a validated, patient‐reported outcome measure to assess the body surface area affected with vitiligo. Information on how to translate the obtained score into extent, severity and impact strata (mild–moderate–severe) is still lacking. Stratification is helpful to define inclusion criteria for trials, enables comparison and pooling of trial results and can be used for epidemiological research. Objectives: The aim was to develop extent, severity and impact strata for the SA‐VES based on validated anchor‐based questions. Methods: In total, 315 patients with vitiligo (non‐segmental; age ≥ 16) recruited at the Ghent University Hospital (Belgium) completed a questionnaire that was conducted in cooperation with the Dutch Society for vitiligo patients to ensure content validity. First three anchor questions included in the questionnaire [Patient Global Assessment (PtGA) for vitiligo extent, severity and impact] were assessed for content validity, construct validity and intrarater reliability. Subsequently, the PtGAs were used to stratify the SA‐VES based on ROC analysis. Results: For all PtGAs (PtGA extent, PtGA severity, PtGA impact), at least 75% of hypotheses evaluated for construct validity were confirmed. Intrarater reliability of all PtGAs was good to excellent (ICCs PtGA extent: 0.623; PtGA severity: 0.828; PtGA impact: 0.851). The optimal cut‐off values of the SA‐VES between the three global categories (mild/limited – moderate – severe/extensive) were 1.05% and 6.45% based on PtGA extent, 2.07% and 4.8% based on PtGA severity and 2% and 3.35% based on PtGA impact. Conclusion: This study provides the first guide for the interpretation of the numerical output obtained by the SA‐VES (vitiligo extent) and enables the translation into a global vitiligo grading for extent, severity and impact. As patients' interpretation of vitiligo extent, severity and impact may vary amongst patients worldwide, future international studies will be required.